The use of the bootstrap method for the assessment of investment effectiveness and risk: The case of confidence intervals estimation for the Sharpe ratio and TailVaR - Jarno Klaudia; Smaga Łukasz (Journal of Banking and Financial Economics (JBFE), 2020)
This paper is aimed at presenting application of bootstrap interval estimation methods to the assessment of financial investment's effectiveness and risk. At first, we give an overview of various methods of bootstrap confidence interval estimation, i.e. bootstrap-t interval, percentile interval and BCa interval. Then, bootstrap confidence interval estimation methods are used to estimate confidence intervals for the Sharpe ratio and TailVaR of the Warsaw Stock Exchange sectoral indices. The results show that the bootstrap confidence intervals of different types are quite similarly positioned for each of the analysed index and measure. Taking into the account the locations of confidence intervals for both the Sharpe ratio and TailVaR, the real estate sector tends to be the most advantageous from the investor's viewpoint.
Keywords: C13; C15; G11; 330; Bootstrap; confidence intervals; Sharpe ratio; TailVaR; stock market index